MENINGKATKAN MINAT BERWIRAUSAHA MELALUI E-COMMERCE, EKSPEKTASI PENDAPATAN DAN MODAL USAHA PADA MAHASISWA PERGURUAN TINGGI DI BANJARNEGARA - Maesaroh, Siti; Asri, Yuliana Nur; Hayati, Sri (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2024)
ABSTRACT The imbalance between the number of jobs and the growth of the productive age population which bring out unemployment, and bachelor graduates contribute 14 percent of it. The research were held in STIE Tamansiswa Banjarnegara and STIMIK Tunas Bangsa Banjarnegara. This study aims to determine the effect of e-commerce, income expectations and business fund toward entrepreneurship interest among collage students in Banjarnegara. This research uses quantitavive methods. Data collection was carried out using a questionnaire and given to a sample of 90 students. The sampling technique in this study used a stratified random sampling method. Data analysis using multiple linear regression. Data analysis techniques in research using validity and reliability test with Cronbach’s Alpha. The classic assumption test includes the normality test, heteroscedasticity test and multicollinearity test. The results of the study show that partiall and simultaneously e-commerce, income expectations and business fund have an effect on entrepreneurial interest. This is evidenced by the calculation results of the SPSS application program, which obtained an Adjusted R Square value of 57.5% while the remaining 42.5% is influenced by other variables. The researcher's suggestion is that students need to increase their interest in entrepreneurship through e-commerce, income expectations and business fund to reduce the unemployment rate of undergraduate graduates.